Aceh Islamic Society (Beliefs in Animism and Dynamism) - Ridwan Muhammad Hasan; Iskandar Ibrahim; Saifuddin Dhuhri (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2018)
The people of Acheh society so immersed in the customary beliefs, traditions and cultures of Hinduism, and belief in large wooden staples such as, banyan trees and ketapang trees, as well as trustworthy objects possessing supernatural powers of animism and dynamism. They are also cling to the teachings of religion that have been abandoned by the former, even though those who bring the teachings are not derived from Islam, indirectly the belief, can form personal in everyday social that is not very memorable. In some parts of the Acheh community who live in rural areas up to now, practice the customs and culture of the tahayul rather than Hindu relics such as, the practice of heresy, superstition and khurafat and has become a practice in its daily that is difficult to be left.